If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 8 = y + 66 Reorder the terms: 8 + 3y = y + 66 Reorder the terms: 8 + 3y = 66 + y Solving 8 + 3y = 66 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 8 + 3y + -1y = 66 + y + -1y Combine like terms: 3y + -1y = 2y 8 + 2y = 66 + y + -1y Combine like terms: y + -1y = 0 8 + 2y = 66 + 0 8 + 2y = 66 Add '-8' to each side of the equation. 8 + -8 + 2y = 66 + -8 Combine like terms: 8 + -8 = 0 0 + 2y = 66 + -8 2y = 66 + -8 Combine like terms: 66 + -8 = 58 2y = 58 Divide each side by '2'. y = 29 Simplifying y = 29
| -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 | | 2y=y+50 | | -80=8(7-2x)-(2x-8) | | 11x-4=10x+25 | | 16y-8(3y-2)=-2424 | | 6x+3+87= | | 13y-17+145=180 | | 1.3y-18=2 | | -10+5x=-55 | | 2x=4x-50 | | 2s=s+22 | | 4h-6=7 | | 2t=t+100 | | 3x+7+56= | | 4b=b+33 | | 2y=y+38 | | 45=8(b-3)+5 | | 8(b+3)=3(2b-4) | | 3x+6+48= | | 8x^3+16x^2+20x+0=0 | | 6n+5=3-5n | | -4(w+6)-6w= | | 6x+x=x+3x+16 | | 4g+5+5g=9m-6 | | 6n+5=3+5n | | x/5-8=13 | | 3n-6=5n-10 | | .12x+1=.880 | | 178=5x+8x | | 9y+84=-8y+2 |